Routledge Handbook of Animal Welfare - Knight, Andrew; Phillips, Clive; Sparks, Paula (Routledge Environment and Sustainability Handbooks, 2023)
This handbook presents a much-needed and comprehensive exploration of the rapidly growing fields of animal welfare and law. In recent years there has been increasing attention paid to our complex, multifaceted relationships with other animals, and in particular, the depth and breadth of various societal uses of animals. This has led to a reconsideration of their moral and social status, which has sometimes challenged the interests of those who use animals. In such a contested domain, sound evidence and reasoning become particularly important. Through firm commitment to such principles, this book explores the biological foundations for the moral consideration of animals and for evolving conceptualisations of animal welfare. It reviews in detail the welfare concerns associated with numerous forms of animal use. The inclusion of key recent developments such as climate change, pandemics, and antimicrobial resistance, ensures this text is among the most current in its field. The ethical implications of the various uses of animals by society are considered, and chapters provide important recommendations for reforms of practice, law, or policy. The status of animal law internationally, and in major world regions, is reviewed. Finally, the book considers human behavioural change and strategies for improving stakeholder communication and education. The handbook is essential reading for students and scholars of animal welfare, animal law and animal ethics everywhere, and for policy-makers and other professionals working in the animal welfare sector.